2014
DOI: 10.1073/pnas.1407808111
|View full text |Cite
|
Sign up to set email alerts
|

H-ferritin–nanocaged doxorubicin nanoparticles specifically target and kill tumors with a single-dose injection

Abstract: An ideal nanocarrier for efficient drug delivery must be able to target specific cells and carry high doses of therapeutic drugs and should also exhibit optimized physicochemical properties and biocompatibility. However, it is a tremendous challenge to engineer all of the above characteristics into a single carrier particle. Here, we show that natural H-ferritin (HFn) nanocages can carry high doses of doxorubicin (Dox) for tumor-specific targeting and killing without any targeting ligand functionalization or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
459
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 417 publications
(477 citation statements)
references
References 43 publications
15
459
0
3
Order By: Relevance
“…Although angiogenesis is enhanced in cancers [ 38 ] suggesting potential competition between endogenous ferritins and H-AFt uptake, a recent study demonstrated successful delivery of doxorubicin encapsulated in H-AFt to tumor sites and in vivo effi cacy. [ 18 ] Thus, we envisage that the observed selective targeting and enhanced effi cacy could be translated in vivo and merits further detailed studies.…”
Section: Release Of Gefi Tinib From H-mentioning
confidence: 91%
See 1 more Smart Citation
“…Although angiogenesis is enhanced in cancers [ 38 ] suggesting potential competition between endogenous ferritins and H-AFt uptake, a recent study demonstrated successful delivery of doxorubicin encapsulated in H-AFt to tumor sites and in vivo effi cacy. [ 18 ] Thus, we envisage that the observed selective targeting and enhanced effi cacy could be translated in vivo and merits further detailed studies.…”
Section: Release Of Gefi Tinib From H-mentioning
confidence: 91%
“…[ 6,9,15,16 ] Recently, selective targeting and cargo delivery with heavy chain apoferritin (H-AFt) was demonstrated both in vitro [ 17 ] and in vivo. [ 18 ] Gefi tinib ("Iressa," ZD1839) is an orally active, epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor. [ 19 ] This receptor family comprises four homologous receptors: EGFR (ErbB1/HER1), HER2 (ErbB2), HER3 (ErbB3), and HER4 (ErbB4), which have an extracellular ligand binding domain, a single hydrophobic trans-membrane domain and a cytoplasmic tyrosine kinase domain.…”
mentioning
confidence: 99%
“…Fts are small enough to penetrate capillary spaces and large enough to avoid renal clearance. Notably, Fts are physiological materials, very soluble in aqueous solutions and in the blood, with low toxicity, susceptible to chemical modifications and being modified by molecular biology techniques [3][4][5][6][7][8][9][10]. Materials such as Fe 3 O 4 , Co 3 O 4 , Mn 3 O 4 , Pt, CoPt, Pd, CdS, CdSe, ZnSe, CaCO 3 , SrCO 3 , Au, Ag and BaCO 3 have been produced and characterized in different ferritin templates [11].…”
Section: Introductionmentioning
confidence: 99%
“…The results were considered to be consistent with another use of hydrazone bond to construct pH-sensitive drug delivery system. 35 DOX almost cannot be released from AFn nanocages in normal tissues due to the pH 7.4 of bodily fluid environment. As for partial acid environment of the tumor tissue, a large number of DOX molecules were slowly released from AFn nanocages after Gd-CDs/AFn (DOX)/FA worked on the tumor position, which greatly improved the treatment efficiency of DOX.…”
Section: Drug Release Kineticsmentioning
confidence: 99%